2021
DOI: 10.1177/08903344211004439
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Views Concerning Human Milk Banking Among Mothers Residing in a Rural Region of Bangladesh

Abstract: Background Human milk banks play an essential role by providing human milk to infants who would otherwise not be able to receive mother’s milk. Study aim To determine the opinions and attitudes among possible donor mothers regarding human milk banks in one rural region in Bangladesh. Methods A prospective, cross-sectional study following a probability type of stratified cluster sampling technique was used. Included in the study ( N = 121) were mothers aged 20–49 years, with at least one child, who was currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
2
15
2
Order By: Relevance
“…The native women and refugees were all Muslims, which explains why they had similar religious concerns. Studies conducted in other Muslim countries also reported religious concerns as the main reason for negative attitudes [6,26]. Similar to our study findings, studies conductedin similar cultures reported that women had the cultural belief of distrusting people they did not know and that personality traits of the donor mother could be transferred to the child through donor milk, in addition to religious concerns [26,27].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The native women and refugees were all Muslims, which explains why they had similar religious concerns. Studies conducted in other Muslim countries also reported religious concerns as the main reason for negative attitudes [6,26]. Similar to our study findings, studies conductedin similar cultures reported that women had the cultural belief of distrusting people they did not know and that personality traits of the donor mother could be transferred to the child through donor milk, in addition to religious concerns [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…More than two-thirds of the women included in this study reported that they had never heard of HMB before. Similar studies report that women have higher awareness in countries where HMBs are used [21][22][23] and levels of awareness about HMB are low in other countries [24][25][26]. Although the respondents' awareness level of HMB was low, at the end of the study, more than half of the respondents supported the founding of an HMB in Turkey.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, there remains a paucity of data documented in Limpopo province involving concerns of healthcare professionals, particularly nurses, regarding breastmilk donation in the Mankweng area. Healthcare professionals, especially nurses, have a responsibility to provide information about breastfeeding and breastmilk expression and are responsible for encouraging mothers to donate to the breastmilk bank, thus increasing the uptake of donor milk practices [ 16 , 18 , 25 , 26 ]. Antenatal education may provide sufficient time for mothers to prepare for lactation prior to admission of the infant to NICU post delivery [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In this article, we recount the educational, financial, and infrastructural challenges that we faced in establishing this religiously compliant and conditionally identified HMB. 23 These services have already begun to positively impact the infant mortality in our region. 21…”
Section: Introductionmentioning
confidence: 99%